Bullying Victimization is Associated with a Significantly Greater Risk of Illicit Substance Use among US Female Adolescents: YRBS 2011 to 2017 - Pontes, Nancy M. H. (Crime & delinquency, 2022)
Bullying victimization among adolescents is associated with increased illicit substance use. This research estimates whether the association between bullying victimization and substance use is significantly greater among female adolescents. Using R software and the national Youth Risk Behavior Survey (2011, 2013, 2014, and 2017), interactions were estimated to determine the association between self-reported school or electronic bullying victimization and previous 30-day alcohol use, binge drinking, marijuana use, cigarette smoking, and electronic vaping product use. Bullying victimization was significantly associated with each of the substance use variables, Effects were significantly greater in female students. Efforts should be put in place in schools and communities to reduce bullying, mitigate the harmful effects of this form of victimization, and reduce illicit substance use.